Editorial. (14th October 2016) - Myles, Pamela
Abstract : Welcome to this Special Issue of tCBT . Our focus in this special edition of the journal is on supervision. Few would argue the vital role of supervision during CBT training and beyond to ensure treatment fidelity to evidence-based protocols. I would like to take this opportunity to thank Professors Derek Milne and Robert Reiser for kindly acting as guest editors. In addition, we are grateful for their fine contributions to the supervision literature in this particular edition of the journal. Thanks too to Professor Cory Newman from the tCBT editorial board for contributing to the overarching paper provided by Professors Milne and Reiser. Thanks also to all the authors for their fine contributions and to our reviewers who gave so generously of their time to comment on the submitted manuscripts. Our intention is to publish one Special Issue a year, next year we look forward to a special edition with a focus on 'complexity' with guest editors Dr Claire Lomax and Dr Stephen Barton from Newcastle University.